Prevention of Criminal Action of Corruption through the Initiation of the Dayak Ngaju Traditional Laws - Kiki Kristanto; Thea Farina; Putri Fransiska Purnama Pratiwi; Libra Adelianty Asuransia (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
Given the complexity of the problem of corruption, it must be treated seriously through a balance of rigorous and precise steps. This step is not only taken by the government and law enforcers, but also by involving the participation of indigenous peoples. In the indigenous Dayak Ngaju community, they are familiar with the principle of not having a bahadat. This principle means that the behavior of life that upholds honesty, equality, togetherness and tolerance and obeying the law (state law, customary law and natural law). According to the author, the existence of the principle of Belom Bahadat can be used as a preventive instrument for the prevention of corruption by government officials in Central Kalimantan Province. This means that there is a contribution of customary law norms to the government's efforts to prevent the occurrence of criminal acts of corruption through the initiation of the belom bahadat principle of Dayak Ngaju customary law.